IMPROVING THE MECHANISMS FOR ORGANIZING EXTRACURRICULAR MUSIC CLUBS - Sattarov Alisher Alikul ugli (Modern American Journals, 2025)
This article explores the effective organization and improvement mechanisms of extracurricular music clubs. It analyzes the role of such clubs in shaping students' aesthetic taste, developing their creative abilities, and fostering respect for national cultural heritage. The paper discusses mechanisms for organizing music club activities based on modern pedagogical technologies, and presents methods for engaging students in musical activities by drawing from both international and local best practices. The study also highlights the forms of extracurricular activities, approaches to their modeling, and their integrative significance in the educational and upbringing process within a scientific and theoretical framework.
Keywords: Extracurricular education, music club, creative activity, aesthetic education, pedagogical technologies, musical taste, national culture, students.